OUTCOME OF LAPAROSCOPIC CHOLECYSTECTOMY IN PATIENTS WITH METABOLIC SYNDROME IN AN ADULT KASHMIRI POPULATION: A PROSPECTIVE HOSPITAL BASED STUDY. (Student's Journal of Health Research Africa, 2023)
Background: The prevalence of Gallbladder stones in India is 6.12 %. Metabolic syndrome is an important risk factor for gallstones. Patients with Metabolic Syndrome seem to be at higher risk of having perioperative complications. Aim: This research aims to study the intraoperative and postoperative complications, duration of hospital stay, and associated mortality in patients with Metabolic syndrome. Material and Methods:A prospective observational study was conducted in the Post Graduate Department of General Surgery, SMHS Hospital, Govt. Medical College, Srinagar on 52 patients with metabolic syndrome undergoing laparoscopic cholecystectomy for cholelithiasis from September 2020 to September 2022 following approval by an institutional ethical committee. All patients underwent laparoscopic cholecystectomy using the standard four-port technique and hospital room setup. Results: The female-to-male ratio in this study was 1.5:1. Hypertension was present in 48%, Diabetes Mellitus in 32.69% of the patients, and Hypothyroidism in 19.23% of the patients. 47 out of 52 (90.3%) of the patients exceeded the waist circumference cut-off for metabolic syndrome according to ATP III criteria. 43 patients (82.6%) had Serum Triglyceride levels exceeding 150mg/dl or were on treatment for the same, HDL ≤ 40mg/dl in men and ≤ 50mg /dl in women was found in a total of 39 (75%) patients, a total of 28 patients (53.8%) had blood pressure ≥ 130/85 mmHg or on antihypertensives. Blood Sugar ≥ 100mg/dl or on hypoglycemic drugs were 21 (40.3%) patients. A total of 2 patients (3.8%)were converted to conventional open cholecystectomy for difficult calots adhesions. 1 patient (1.9%) had a bile leak and 1 patient (1.9%) had post-operative bleeding, Port site hernia in 1 patient (1.9%) and 2 patients (3.8%) developed surgical site infection. Conclusion: Laparoscopic Cholecystectomy is an effective procedure with excellent functional outcomes in patients with Metabolic Syndrome.
Keywords: Metabolic Syndrome; Laparoscopic Cholecystectomy; Cholelithiasis; Bile leak; Port site hernia